Laughter-induced headache? Yes, it is Possible! - Soumya Bhowmik; Kuljeet Singh Anand (Indian Journal of Medical Specialities)
There have been well-known headache precipitants already documented in the literature. Laughter has previously been found as a rare trigger of headache in some individuals. Laughter-induced headache is a rare type of triggered headache which can share some similarities with primary cough headache or primary exercise headache. We report a case of abrupt onset, bilateral temporo-occipital headache, typically triggered exclusively by loud laughter in a 30-year-old male, with normal neurological examination and neuroimaging brain. The patient has shown some excellent responses to treatment with sodium valproate.